2020
DOI: 10.1051/e3sconf/202019503013
|View full text |Cite
|
Sign up to set email alerts
|

A physical model for the interaction between unsaturated soils and retaining structures

Abstract: Temporary and permanent retaining structures interact with soils that are usually in unsaturated conditions. In this work, a 1g-scale physical model is presented to investigate the interactions between retaining walls and unsaturated soils. The physical model is equipped with a water-filled hydraulic cylinder connected to a pressure-volume controller to measure the horizontal component of the later earth thrust and high capacity tensiometers to measure soil matric suction. A system of low-friction linear guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Some of the appeal derives from the potential use of unsaturated soil mechanics as a tool to reduce the carbon footprint of various civil engineering applications [1][2][3][4][5]. For instance, Speranza et al [6] suggested that the increase in strength resulting from the suction s may be conveniently adopted to reduce the overdesign of the retaining structures in temporary works, leading to a reduction in emissions and materials used. Dynamic centrifuge tests on a shallow foundation performed by Borghei et al [7] indicated that groundwater fluctuations significantly affect the seismic response of geotechnical systems and that neglecting them does not necessarily lead to safer or more economical design solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the appeal derives from the potential use of unsaturated soil mechanics as a tool to reduce the carbon footprint of various civil engineering applications [1][2][3][4][5]. For instance, Speranza et al [6] suggested that the increase in strength resulting from the suction s may be conveniently adopted to reduce the overdesign of the retaining structures in temporary works, leading to a reduction in emissions and materials used. Dynamic centrifuge tests on a shallow foundation performed by Borghei et al [7] indicated that groundwater fluctuations significantly affect the seismic response of geotechnical systems and that neglecting them does not necessarily lead to safer or more economical design solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have also incorporated unsaturated soil mechanics in the geotechnical analysis of various problems, such as in situ testing, seismic response of foundations, and the analysis of retaining structures, to mention a few [6][7][8][9]. Komolafe and Ghayoomi [10] recently incorporated suction stress in the determination of the theoretical ultimate lateral resistance of cohesionless soils.…”
Section: Introductionmentioning
confidence: 99%